Peranan Qarā`In Dalam Penerimaan Hadis Ḍa’īf Di Sisi Mazhab Al-Shāfi’ī - Ahmad Hafiz Mohd Rozmizi; Mohd Khafidz Soroni; Thuraya Ahmad (Universiti Sains Islam Malaysia, 2026)
Journal of Hadith Studies, Volume 10 Issue 2 Page (121–136)